Potential savings from consumer-driven health plans. (2nd October 2021) - Ferguson, William; White, Brittany S.; McNair, Jessica; Miller, Christopher; Wang, Bojing; Coustasse, Alberto
ABSTRACT: Consumer-driven health plans (CDHPs) have been identified as a high-deductible insurance option increasing consumer responsibility while decreasing healthcare expenditures. There has been an increasing need for these plans because they can help to control healthcare costs and the increasing healthcare utilization. As the use of these plans has expanded, educated consumers have become more engaged in their healthcare services and have increased demands for transparency of healthcare costs. The methodology for this study was a literature review using 37 sources. The purpose of this study was to determine if CDHPs have created financial savings by increasing transparency of healthcare cost and decreasing moral hazard. This review suggested that consumers of CDHPs are at a greater risk of moral hazard, yet participants still utilized healthcare in times of necessity. The utilization of CDHPs can both alter consumer's utilization of healthcare services and decrease the cost to the consumer while increasing cost transparency. By focusing on cost, price transparency, it was found that participants were more educated of their healthcare insurance and spent less money than participants in other models of healthcare such as Preferred Provider Organizations or Health Maintenance Organizations.